Survival in 200 patients treated by haemodialysis and renal transplantation. Issue 6058 (12th February 1977) - Henari, F Z; Gower, P E; Curtis, J R; Eastwood, J B; Phillips, M E; Greatbatch, M L; Williams, G B; Gordon, E M; Boyd, P J; Stubbs, R K; de Wardener, H E
Abstract : The survival rates in 200 patients with terminal renal failure treated by maintenance haemodialysis and renal transplantation were analysed. The overall survival rate (+/- SE) was 81-4 +/- 3% at two years, 68-4 +/- 4% at five years, and 60-8 +/- 4-8% at eight years. Survival was inversely related to age: in those aged 15-34 years overall survival was 89-7 +/- 3-7% at two years, 87-8 +/- 4-1% at five years, and 83-9 +/- 5-5% at eight years. Eighty per cent of the surviving patients were able to work full time. The survival rate in patients returned to dialysis after graft rejection was 87-5% +/- 8-3 at three years.